Effect of initial dislocation density on the plastic deformation response of 316L stainless steel manufactured by directed energy deposition - Li, Shihao (2022)
The relationship between the microstructural features (such as the solidification cells and initial dislocation densities) and the tensile properties of alloys additively manufactured (AM) using techniques such as laser powder bed fusion (L-PBF) and directed energy deposition (DED) is yet to be firmly established. In this work, a detailed investigation into the structure-property relations in DED 316L austenitic stainless steel (316L SS) was conducted. The microstructural parameters were varied systematically by changing the laser energy employed. Results show that while the sizes of grains and cells and the volume fraction of the oxide particles increase with increasing laser energy, the dislocation density decreases. Importantly, a uniform distribution of dislocations, instead of dislocation networks that are reported in many AM alloys, was observed. The connection between these microstructural features and the yield strength and work hardening capability of the DED 316L SS, which vary systematically with the laser energy, are explored. The correlation shows that a Hall-Petch type relation cannot capture the measured yield strength variation. Instead, the initial dislocation density dominates both the yield strength and the work hardening behavior. These results suggest a strategy for manipulating the mechanical performance in AM alloys through the control of dislocation densities and their distribution.